High Lysyl Oxidase (LOX) in the Non-Malignant Prostate Epithelium Predicts a Poor Outcome in Prostate Cancer Patient Managed by Watchful Waiting. - Maria Nilsson; Christina Hägglöf; Peter Hammarsten; Elin Thysell; Pär Stattin; Lars Egevad; Torvald Granfors; Emma Jernberg; Pernilla Wikstrom; Sofia Halin Bergström; Anders Bergh (PLoS ONE, 2015)
Lysyl oxidase (LOX) has been shown to both promote and suppress tumor progression, but its role in prostate cancer is largely unknown. LOX immunoreactivity was scored in prostate tumor epithelium, tumor stroma and in the tumor-adjacent non-malignant prostate epithelium and stroma. LOX scores in tumor and non-malignant prostate tissues were then examined for possible associations with clinical characteristics and survival in a historical cohort of men that were diagnosed with prostate cancer at transurethral resection and followed by watchful waiting. Men with a low LOX score in the non-malignant prostate epithelium had significantly longer cancer specific survival than men with a high score. Furthermore, LOX score in non-malignant prostate epithelium remained prognostic in a multivariable analysis including Gleason score. LOX score in prostate tumor epithelium positively correlated to Gleason score and metastases but was not associated with cancer survival. LOX score in tumor and non-malignant prostate stroma appeared unrelated to these tumor characteristics. In radical prostatectomy specimens, LOX immune-staining corresponded to LOX in-situ hybridization and LOX mRNA levels were found to be similar between tumor and adjacent non-malignant areas, but significantly increased in bone metastases samples. LOX levels both in tumors and in the surrounding tumor-bearing organ are apparently related to prostate cancer aggressiveness.